Microbubbles containing lysolipid enhance ultrasound‐mediated blood–brain barrier breakdown in vivo - Vince, O; Peeters, S; Johanssen, VA; Gray, M; Smart, S; Sibson, NR; Stride, E (Wiley, 2020)
Ultrasound and microbubbles (MBs) offer a noninvasive method of temporarily enhancing blood–brain barrier (BBB) permeability to therapeutics. To reduce off‐target effects, it is desirable to minimize the ultrasound pressures required. It has been shown that a new formulation of MBs containing lysolipids (Lyso‐MBs) can increase the cellular uptake of a model drug in vitro. The aim of this study is to investigate whether Lyso‐MBs can also enhance BBB permeability in vivo. Female BALB/c mice are injected with either Lyso‐MBs or control MBs and gadolinium‐DTPA (Gd‐DTPA) and exposed to ultrasound (500 kHz, 1 Hz pulse repetition frequency, 1 ms pulse length, peak‐negative pressures 160–480 kPa) for 2 min. BBB permeabilization is measured via magnetic resonance imaging (7.0 T) of Gd‐DTPA extravasation and subsequent histological examination of brain tissue to assess serum immunoglobulin G (IgG) extravasation (n = 8 per group). An approximately twofold enhancement in BBB permeability is produced by the Lyso‐MBs at the highest ultrasound pressure compared with the control. These findings indicate that modifying the composition of phospholipid‐shelled MBs has the potential to improve the efficiency of BBB opening, without increasing the ultrasound pressure amplitude required. This is particularly relevant for delivery of therapeutics deep within the brain.